Functional Studies of Prehistoric Artefacts and their Socio-economic Meaning - Pawlik, Alfred (Archīum Ateneo, 2020)
Traceology continues to be the major method for the identification of prehistoric activities using tools made of lithic and organic materials since Sergei A. Semenov's fundamental work 'Prehistoric Technology' introduced this method to prehistorians worldwide over half a century ago (Semenov 1964). The analysis of microscopic wear traces and use-related residues provides significant information on various important aspects of archaeological research. Among them are questions on site functions and activities carried out in prehistoric settlements, or the reconstruction of archaeologically invisible components of complex tool technology, for instance hafting and composite tool design. Traceology has also significantly contributed to the debates on human behavioural complexity, adaptation to changing environments and cultural and cognitive advancement as well as other aspects of the evolution of the human intellect.